Living labs as orchestrators in the regional innovation ecosystem: a conceptual framework - Janin Fauth; Kevin De Moortel; Dimitri Schuurman (Journal of Responsible Innovation)
This research explores the conceptual integration of Living Labs (LLs) into the Regional Innovation Ecosystem (RIE) to understand their potential as facilitators of Responsible Innovation. While previous studies explored the role of Living Labs, they lack comprehensive integration strategies for addressing wicked problems. A conceptual framework is developed to understand the main role, detailed functions, and key elements for integration. Seven expert interviews were conducted to develop the conceptual framework, using the Interuniversity Microelectronics Centre (imec) within the Flemish Innovation Ecosystem as empirical context. The findings emphasise Living Labs as central orchestrators, enabling user-centric innovation, real-world experimentation, and stakeholder engagement. We identify four key elements that facilitate the proposed integration: government policy and funding, strategic integration, formal collaborations, and proof of concept. These findings have implications for advancing the theoretical understanding of Living Labs' integration into the Regional Innovation Ecosystem, and for practitioners who aim to foster Responsible Innovation.